VARIETIES OF BAQLAJON WITH VALUABLE FARM CHARACTERISTICS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article presents the results obtained at the Surkhandarya Scientific Experimental Station of the Institute of Vegetable Growing, Melon Crops and Potato Growing in 2021-2023 on early-ripening, nematode-resistant varieties and lines of eggplant. The study showed that the highest total yield was observed in the TRIAL sample brimdal 972 variety and was 35.3% higher than in the standard variety, with a yield of 82.1 t/ha.